Partially inbred maize lines in topcrosses and hybrid performance - Fialho dos Reis, Edésio; dos Santos Candido, Willame; Lima Costa, Maraiza; Soares Lima Ragagnin, Angelita Lorrayne; Somera, Andreia (Revista Ceres, 2025)
In plant breeding programs, the selection of potential progenies in early generations of inbreeding is an essential step. Considering that, the adoption of topcrosses helps the breeder in the selection, this study aimed to verify the potential of S2 strains for synthesis of synthetic varieties and to obtain experimental information on yield and agronomic potential of topcross hybrids. As such, 75 topcross hybrids were generated from crossing 75 S2 lines with F2 generation of the commercial hybrid. The 75 hybrids were grown in a field, along with two commercial hybrids in a randomized complete block design with 4 replicates and in 4-meter plots. Flowering, plant height, height, diameter, length and weight in the ear, and grain yield traits were examined. Analysis of variance was performed, the combining ability was estimated, and, from the means, the Scott & Knott test was conducted. So, the topcross hybrids that distinguished themselves for grain yield were those composed by lines 67, 14, 44, and 69, presenting high CGA, therefore indicating good potential for producing synthetic or base population. For the other traits of agronomic interest that were assessed in maize, a potential for selection with different focuses was found: reduction of cycle and height and increase in length and diameter of the ear.